Jesuit strategy in Japan and India in the 16th Century as a precursor to modern Western “Soft Power” - Volosyuk, O.V.; Nesterova, O.A.; Solodkova, O.L. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
The principles of “soft power”, within the context of the historical development of international relations both on the worldwide and regional levels, had been applied in the East and in the West long before the aforementioned theories appeared. It was the Jesuits in the 16th Century who developed strategies of influence and were pioneers in the introduction of “soft” methods of leverage in international communication practice. In today’s world, which is witnessing an increase in the role of the religious factor in international relations, it is important to understand how to identify these achievements, and correct the mistakes of these early strategies, based on the practices of Francis Xavier in Japan and of Antoni de Montserrat in the Mughal Empire. An attentive and thorough study of the Jesuits’ experience is of great importance in understanding contemporary processes of international interaction from a “soft power” point of view.